The Red Zone of Islamic Microfinance Institutions (BMTs) in South Sulawesi: A Globalization Perspective - Syaparuddin Syaparuddin (AIUA Journal of Islamic Education, 2019)
The aim of BMTs established was providing business development services and community empowerment in the rural area, through financing in micro- scale businesses to their members and the community, deposit management, and providing business development consulting services based on sharia principles. In South Sulawesi, BMTs seem to be unable to carry out their main objective, even though their existence is as the front guard in moving the economy of the people in the rural area. Therefore, this study is present to solve this problem. So the purpose of this study is to analyze the impact of financial sector digitilization on BMTs in South Sulawesi, the efforts of digital transformation taken and the use of Information Technology in their management in the globalization era. The data used to discuss the three things above were collected via an interview method, a focus discussion group and documentation. These data were analyzed by a combination of globalization concepts according to Scholte and Bartelson. The results of this study showed that if BMTs in South Sulawesi are unable to adapt to IT in serving the community in this globalization era, they will lose their market share so that their conditions must be on the red zone. This should not be allowed to happen because BMTs are as the front guard in moving the economy of the people in the rural area